2019
DOI: 10.1155/2019/5179081
|View full text |Cite
|
Sign up to set email alerts
|

A Health Records Review of Outpatient Referrals from the Emergency Department

Abstract: Objectives Many patients discharged home from the emergency department (ED) require urgent outpatient consultation with a specialty service. We sought to identify the best- and worst-performing services with regard to time to outpatient consultation, the proportion of patients lost to follow-up, the rate of related return ED visits prior to consultation, and common strategies used by our top-performing clinics. Methods We conducted a health records review of The Ottawa Hospital ED visits during four 1-week per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Despite the incidence of eye-related visits to GES, several studies have highlighted the lack of comfort general emergency physicians have in managing eye-related issues. [18][19][20] Ophthalmology, along with orthopedics, represents one of the most frequently consulted services by GESs [16,21].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the incidence of eye-related visits to GES, several studies have highlighted the lack of comfort general emergency physicians have in managing eye-related issues. [18][19][20] Ophthalmology, along with orthopedics, represents one of the most frequently consulted services by GESs [16,21].…”
Section: Discussionmentioning
confidence: 99%
“…A sampling technique was employed in which data were collected from the first seven days of each month. This sampling method was derived from a study by Prudomme et al looking at volumes of outpatient referrals in an ED [ 1 ]. This technique was selected in order to account for potential daily, monthly, or seasonal variation in pager volumes.…”
Section: Methodsmentioning
confidence: 99%
“…A significant degree of work for residents on call comes from answering and managing pages. On-call services in ophthalmology receive high volumes of consults, often in the form of pages requiring urgent patient assessment [ 1 , 2 ]. Relative to other surgical specialties, the profile of commonly received pages in ophthalmology may be different, but has never previously been studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…f the 2 million ophthalmology-related emergency department (ED) encounters that occur annually in the US, 44.3% to 76.6% are for nonemergent conditions that require follow-up at an outpatient eye clinic. [1][2][3] Follow-up is important for treatment continuation, 4 correction of misdiagnosis, 5,6 avoiding return ED visits, 7 and transition to long-term ophthalmic care. However, literature has reported that 25.2% to 39.0% of patients seen for eye-related issues in the ED do not receive recommended follow-up care.…”
mentioning
confidence: 99%